Design and implementation of huvigation for the visually impaired - Jang, Jinhyeok; Lee, Youngseok (International Journal of Engineering and Technology, 2018)
Background/Objectives: Visual impairments should take the risk alone, we need to design a Huvigation because it is necessary to study the route and surrounding dangerous obstacles with a convenient device.Methods/Statistical analysis: Set the destination using voice recognition and braille input device to help the users find the way, guided by voice when user want, obstacles are read using an ultrasonic sensor. In the obstacle detection method, prioritize in the direction of things by three ultrasonic sensors. And the user recognize the direction of things reduces the probability of strike the object than other functions.Findings: The proposed system can set the destination using speech recognition or a braille input device. The information is transmitted to a navigation web page linked with the input destination, and navigation is guided using the navigation function. This device transmits the information received using a speaker. This device receives information from the ultrasonic sensor. When objects come into range, a voice is transmitted to the user to prevent collision. When the user arrives at the destination, It announces the arrival using the speaker, and wait for the next command.Improvements/Applications: The safety of the user is ensured through three ultrasonic sensors. Every time the user moves and checks the location information and provides movement information.
Keywords: Visually Impaired; Cane; Navigation; Road Master; Obstacles Detection; Ultrasonic Sensors